Who's Behind the Lens?: A Reflexive Analysis of Roles in Participatory Video Research. (April 2018) - Whiting, Rebecca; Symon, Gillian; Roby, Helen; Chamakiotis, Petros
This article applies paradox as a metatheoretical framework for the reflexive analysis of roles within a participatory video study. This analysis moves us beyond simply describing roles as paradoxical, and thus problematic, to offer insights into the dynamics of the interrelationship between participant, researcher, and video technology. Drawing on the concept of "working the hyphens, " our analysis specifically focuses on the complex enactment of Participation-Observation and Intimacy-Distance "hyphen spaces." We explore how video technology mediates the relationship between participant and researcher within these spaces, providing opportunities for participant empowerment but simultaneously introducing aspects of surveillance and detachment. Our account reveals how video study participants manage these tensions to achieve participation in the project. It examines the roles for the researched, the technology, and the researchers that are an outcome of this process. Our analysis advances methodology by bringing together a paradox perspective with reflexive work on research relationships to demonstrate how we can more adequately explore tensions in research practice and detailing the role of technology in the construction and management of these tensions.